The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1186/s13011-019-0240-3
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence of alcohol use disorders among people living with HIV/AIDS: a systematic review and meta-analysis

Abstract: BackgroundAlcohol use disorder (AUD) is common among people living with HIV/AIDS (PLWHA) and associated with a greater risk of poor medication adherence, unsafe sexual behaviors as well as poor quality of life. To our knowledge, there is no previous systematic review and meta-analysis that reported the pooled prevalence estimate of AUD among PLWHA. Therefore, this review aimed to systematically review the available studies on the prevalence of AUD among PLWHA and forward possible recommendations for future cli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
107
4
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(128 citation statements)
references
References 49 publications
6
107
4
2
Order By: Relevance
“…24.00, 35.00). This result was consistent with the global average prevalence of AUD among individuals living with HIV/AIDS (29.80%) (55).…”
Section: Discussionsupporting
confidence: 91%
“…24.00, 35.00). This result was consistent with the global average prevalence of AUD among individuals living with HIV/AIDS (29.80%) (55).…”
Section: Discussionsupporting
confidence: 91%
“…The average prevalence of alcohol use disorder among tuberculosis patients using the random effect model was found to be 30% (95% CI: 24.00, 35.00). This result was consistent with the global average prevalence of AUD among individuals living with HIV/AIDS (29.80%) (55).…”
Section: Discussionsupporting
confidence: 91%
“…Considering year of publication, the average prevalence of AUD in studies published before 2011 [9,12,15], 2011-2015 [10,13,14,19,[21][22][23]51], and after 2015 [7,8,11,17,18,20,27,28,49,50,52] Table 1 Characteristics of studies on the 1 year prevalence alcohol use disorders among HIV/AIDS patients on ART which are incorporated in the narrative as well as meta-analysis according to author first name, year of publication, setting of study, design, sample size, assessment instrument, study population and magnitude of alcohol use disorder (Fig. 3) and ( Table 2).…”
Section: The 1 Year Prevalence Of Alcohol Use Disorders Among Hiv/aidmentioning
confidence: 99%
“…The prevalence of AUD in patients with retroviral infection has been evidenced higher than people without retroviral infection or the general public [6]. A systematic review and meta-analysis study by Duko et al 2019 [7] showed that the average worldwide prevalence of AUD among patients with HIV/AIDS was found to be 29.8%. Other earlier studies in Africa reported that the prevalence of AUD ranges from 17 to 39.4% in Nigeria [8][9][10], 1.4 to 33% in Uganda [11][12][13][14], 6.6 to 48.5% in South Africa [15][16][17][18], 5.4 to 33% in Kenya [19][20][21][22], and 14.8% in Zambia [23].…”
Section: Introductionmentioning
confidence: 99%